Peran Bank Sampah dalam Implementasi Program “Semarang Bersih”: (Studi Kasus Pengelolaan Sampah Berbasis Komunitas Menuju Kota Berkelanjutan) - Elsa Ananda Meylanisa; Afnan Nanda; Muhammad Faiz Zalfa; Adelya Marsyanda; Monika Fransiska; Ivan Adicahyono (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
The problem of waste management in Indonesia is increasingly pressing, with more than 11.3 million tons of waste unmanaged each year. Semarang City, which produces 1,300 tons of waste per day, faces similar challenges with suboptimal waste collection rates. In response to this crisis, the Semarang City Government launched the “Clean Semarang” program with a zero waste approach by strengthening more than 150 community-based waste banks. This study uses a qualitative case study approach to analyze the implementation of the program, the role of waste banks, management challenges, and their contribution to SDGs 11.6 and 12.5. The results show that waste banks play a role in environmental education, reducing waste to landfills, economic empowerment, and cross-sector collaboration. However, unequal community participation, limited infrastructure, and policy barriers remain challenges. This program has proven to be relevant in encouraging sustainable waste management and can be a model for replication in other cities.